Production smoothing and the shape of the cost function - Marzio Galeotti; Luigi Guiso; Brian Sack; Fabio Schiantarelli (Fondazione Eni Enrico Mattei (FEEM), 1997)
We present estimates of inventory models based on firm level panel data and investigate whether over-simplified specification of the production technology may account for the frequent failure to find technological incentives to smooth production in the context of the standard linear-quadratic model of inventory behavior. In particular, we argue that if the role of quasi-fixed factors is not modeled properly, this may lead to inconsistent estimates of marginal costs and, therefore, to erroneous conclusions about the convexity/concavity of the cost function. The model is accordingly extended to allow for a general restricted quadratic cost function, on the assumption that capital is costly to adjust. The evidence obtained by estimating the standard inventory model on a panel of Italian manufacturing firms suggests that marginal costs are decreasing. However, this result is overturned when one allows for the general quadratic cost function with capital as a quasi-fixed input, implying that the firm's technology provides incentives to smooth production.
Keywords: D21; D92; E22; 330; Inventories; Production Smoothing; Cost Function; Lagerzyklus; Kostenfunktion; Theorie